(untitled) (Dialogos, 2017)
Neste ensaio, proponho uma discussão sobre as relações entre o gênero biográfico, a ficção e a história, através da análise do prefácio das Vies imaginaires, de Marcel Schwob. A proposta é seguir alguns argumentos do escritor francês, tomando-os como uma espécie de roteiro para um exercício reflexivo em torno das transmutações da biografia, relacionando-a ao contexto da modernização da escrita histórica, ao longo do século XIX e décadas iniciais do XX. Abstract The lives of a genre: biography, history, fiction In this essay, I propose a discussion on the relationship between the biographical genre, fiction and history, by analyzing the preface of Marcel Schwob’s Vies imaginaires. The proposal is to follow some arguments of the French writer, taking them as a kind of script for a reflexive exercise around the transmutations of biography, relating it to the context of the modernization of historical writing, throughout the nineteenth century and early twentieth decades.